Global differentiable dynamics : proceedings - Regional conference on Global Differentiable Dynamics, Case western Reserve University, Cleveland, Ohio June 2-6 1969; Hajek, Otomar; Lohwater, A. J.; McCann, Roger (Berlin : Springer-Verlag, 1971)
41